Perjanjian Pembiayaan Ijarah ‎ di Lingkungan Bank Syariah - Soeko Tribekti Rahardjo (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2016)
Abstract: Global crisis is happening now lead efforts to find the root of the problem, one application of the system of usury which has worldwide. This raises fresh air for the implementation of the Islamic banking system, which has now entered two decades. One model of financing in Islamic banking is ijarah, which can be equated with a lease, hire wage, or leasing. Which makes the development of Islamic banking in Indonesia is the presence of Act No. 3 In 2006 the Religious Courts, which provide clarity and certainty to the community and economic actors sharia, especially in the field of Islamic banking. It is related to its jurisdiction examine, decide and resolve cases the